2005
DOI: 10.1210/en.2004-0836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Potent Luteinizing Hormone-Releasing Activity of KiSS-1 Peptide, the Natural Ligand of GPR54

Abstract: Loss-of-function mutations of the gene encoding GPR54, the putative receptor for the KiSS-1-derived peptide metastin, have been recently associated with hypogonadotropic hypogonadism, in both rodents and humans. Yet the actual role of the KiSS-1/GPR54 system in the neuroendocrine control of gonadotropin secretion remains largely unexplored. To initiate such analysis, the effects of KiSS-1 peptide on LH secretion were monitored using in vivo and in vitro settings under different experimental conditions. Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
265
1
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(293 citation statements)
references
References 35 publications
19
265
1
8
Order By: Relevance
“…For hormonal tests, a protocol of intracerebral injection of kisspeptin-10 was applied to control and STZinjected animals. To allow delivery of kisspeptin into the lateral cerebral ventricle, the animals were implanted under ether anesthesia with intracerebroventricular cannulae lowered to a depth of 3 mm beneath the surface of the skull; the insert point was 1 mm posterior and 1.2 mm lateral to bregma, as described previously (22,29,31). Two doses of kisspeptin-10 were tested: 1 nmol (maximal) and 10 pmol (submaximal) in 10 l. Blood samples (300 l) were obtained by jugular venipuncture under light ether anesthesia before (0 min) and at 15 and 60 min after kisspeptin injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For hormonal tests, a protocol of intracerebral injection of kisspeptin-10 was applied to control and STZinjected animals. To allow delivery of kisspeptin into the lateral cerebral ventricle, the animals were implanted under ether anesthesia with intracerebroventricular cannulae lowered to a depth of 3 mm beneath the surface of the skull; the insert point was 1 mm posterior and 1.2 mm lateral to bregma, as described previously (22,29,31). Two doses of kisspeptin-10 were tested: 1 nmol (maximal) and 10 pmol (submaximal) in 10 l. Blood samples (300 l) were obtained by jugular venipuncture under light ether anesthesia before (0 min) and at 15 and 60 min after kisspeptin injection.…”
Section: Methodsmentioning
confidence: 99%
“…These findings drew immediate attention to the previously unsuspected neuroendocrine facet of kisspeptins, ligands of GPR54, which are structurally related peptides generated by the differential proteolytic processing of a common precursor encoded by the metastasis suppressor KiSS-1 gene (19 -21). Indeed, a wealth of data has now demonstrated that kisspeptins are potent elicitors of the GnRH/gonadotropin axis in a number of species, including humans (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and mechanistic studies have suggested a relevant role of KiSS-1 signaling in puberty onset in rodents and primates (24,27). Moreover, hypothalamic expression of the KiSS-1 gene appeared to be maximal at puberty and regulated by sex steroids (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…The apparent lack of kisspeptin's effect on the pituitary was confirmed in the rat by Matsui et al (2004), who reported that another GnRH antagonist, cetrorelix, also blocks the kisspeptin-induced release of LH and FSH. However, in vitro, kisspeptin has been shown to stimulate LH release and augment GnRH-stimulated FSH release from pituitary explants derived from peripubertal male rats -albeit modestly (Navarro et al 2005a(Navarro et al , 2005b; nevertheless, kisspeptin has little or no effect on the release of either LH or FSH from primary cultures of pituitary cells derived from rats (Matsui et al 2004). Moreover, another study reports that kisspeptin has no effect on LH and FSH release from rat pituitary explants, yet it stimulates GnRH secretion from hypothalamic explants (Thompson et al 2004).…”
Section: How Kiss1 Got Its Namementioning
confidence: 99%
“…Kisspeptin (Kiss1) neurons in the hypothalamic anteroventral periventricular nucleus (AVPV) send fibers to GnRH neurons, and it has become apparent that this input serves as a powerful impetus for elicitation of the LH surge (e.g. Gottsch et al 2004, Navarro et al 2005. This study examined the relationship between the expression of Kiss1 mRNA in the AVPV and the surge following 1 and 4 days of ATRZ exposure.…”
Section: Introductionmentioning
confidence: 99%